Coolies, capital, and colonialism studies in Indian labour history - Behal, Rana Partap (International review of social history Special issue, 2006)
Introduction / Sabyasachi Bhattacharya -- Working across the seas : Indian maritime labourers in India, Britain, and in between, 1600-1857 / Michael H. Fisher -- The brickmakers' strikes on the Ganges Canal in 1848-1849 / Jan Lucassen -- On the move : circulating labour in pre-colonial, colonial, and post-colonial India / Ian J. Kerr -- Mobility and containment : the voyages of South Asian seamen, c. 1900-1960 / Ravi Ahuja -- Power structure, discipline and labour in Assam tea plantations during colonial rule / Rana P. Behal -- "Following custom?" : representations of community among Indian immigrant labour in the West Indies, 1880-1920 / Prabhu P. Mohapatra -- Masculinity, respect, and the tragic : themes of proletarian humor in contemporary industrial Delhi / Shankar Ramaswami -- Stretching labour historiography : ideas from South Asia / Willem van Schendel -- War on the shopfloor / Rajnarayan Chandavarkar